Structural insights into semicrystalline states of electrospun nanofibers: a multiscale analytical approach. Issue 15 (28th March 2019) - Maurya, Anjani K.; Weidenbacher, Lukas; Spano, Fabrizio; Fortunato, Giuseppino; Rossi, René M.; Frenz, Martin; Dommann, Alex; Neels, Antonia; Sadeghpour, Amin
Abstract : For potential applications in the biomedical domain, we report a comprehensive roadmap towards structural hierarchy and anisotropy in electrospun fibers based on scattering and diffraction studies. Abstract : A dedicated nanofiber design for applications in the biomedical domain is based on the understanding of nanofiber structures. The structure of electrospun nanofibers strongly influences their properties and functionalities. In polymeric nanofibers X-ray scattering and diffraction methods, i.e. SAXS and WAXD, are capable of decoding their structural insights from about 100 nm down to the Angström scale. Here, we present a comprehensive X-ray scattering and diffraction based study and introduce new data analysis approaches to unveil detailed structural features in electrospun poly(vinylidene fluoride- co -hexafluoropropylene) (PVDFhfp) nanofiber membranes. Particular emphasis was placed on anisotropic morphologies being developed during the nanofiber fabrication process. Global analysis was performed on SAXS data to derive the nanofibrillar structure of repeating lamella crystalline domains with average dimensions of 12.5 nm thickness and 7.8 nm spacing along with associated tie-molecules. The varying surface roughness of the nanofiber was evaluated by extracting the Porod exponent in parallel and perpendicular direction to the nanofiber axis, which was further validated by Atomic Force Microscopy. Additionally, the presence of a mixture of the monoclinic alpha and the orthorhombic beta PVDFhfp phases both exhibiting about 6% larger unit cells compared to the corresponding pure PVDF phases was derived from WAXD. The current study shows a generic approach in detailed understanding of internal structures and surface morphology for nanofibers. This forms the basis for targeted structure and morphology steering and the respective controlling during the fabrication process with the aim to engineer nanofibers for different biomedical applications with specific requirements.